2021
DOI: 10.1101/2021.08.09.455633
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Benchmarking artificial intelligence methods for end-to-end computational pathology

Abstract: Artificial intelligence (AI) can extract subtle visual information from digitized histopathology slides and yield scientific insight on genotype-phenotype interactions as well as clinically actionable recommendations. Classical weakly supervised pipelines use an end-to-end approach with residual neural networks (ResNets), modern convolutional neural networks such as EfficientNet, or non-convolutional architectures such as vision transformers (ViT). In addition, multiple-instance learning (MIL) and clustering-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
3
1

Relationship

6
1

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 45 publications
2
21
0
Order By: Relevance
“…DeepMed is a straightforward, scalable, and powerful implementation of end-to-end weakly supervised Deep Learning in histology, as demonstrated here. New technologies, such as multiple instance learning 32 and vision transformers 12 , have recently been investigated for such weakly supervised prediction challenges. Although there is limited data on these strategies' realworld performance, some of them may become the de-facto state of the art in the future.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DeepMed is a straightforward, scalable, and powerful implementation of end-to-end weakly supervised Deep Learning in histology, as demonstrated here. New technologies, such as multiple instance learning 32 and vision transformers 12 , have recently been investigated for such weakly supervised prediction challenges. Although there is limited data on these strategies' realworld performance, some of them may become the de-facto state of the art in the future.…”
Section: Discussionmentioning
confidence: 99%
“…For example, multiple analysis pipelines have been developed between 2018 and 2021 to predict the mutations of oncogenic driver genes from H&E WSI. 3,5,[9][10][11][12] The overall design of these pipelines is largely identical: they load a WSI, tessellate it into tiles, perform data augmentation and/or normalization, train a CNN, deploy the network on tiles from test patients and use an aggregation function to pool the tile-level predictions on a patient level. 9…”
Section: Introduction End-to-end Deep Learning In Computational Pathologymentioning
confidence: 99%
“…For prediction of molecular features from image data, we adapted our weakly-supervised prediction pipeline "Histology Image Analysis (HIA)" 9 which was demonstrated to outperform similar approaches for mutation prediction in a recent benchmark study. 37 Briefly, the workflow entails the following steps: As preprocessing step, high resolution WSIs were tessellated into patches of size ሺ512 ൈ 512 ൈ 3ሻ pixels and color-normalized. 38 During this process, blurry patches and patches with no tissue are removed from the data set using canny edge detection in OpenCV.…”
Section: Deep Learning and Swarm Learning Methodsmentioning
confidence: 99%
“…38 During this process, blurry patches and patches with no tissue are removed from the data set using canny edge detection in OpenCV. 37 Subsequently, we used ResNet18 to extract a ሺ512 ൈ 1ሻ feature vector from 150 randomly selected patches for each patient, as previous work showed that 150 patches are sufficient to obtain robust predictions. 9 Feature vectors and patient-wise target labels (BRAF or MSI status) served as input to a fully connected classification network (FCN).…”
Section: Deep Learning and Swarm Learning Methodsmentioning
confidence: 99%
“…To date, only very few studies have investigated the use of ViTs in computational pathology. 23,24 Technical studies have described improved robustness of ViTs to adversarial changes to the input data, but this has not been explored in medical applications. 25–27…”
Section: Introductionmentioning
confidence: 99%